Digital Technologies and Financial Performance in Local Government in Uganda: A Case Study of Kabale District. - Mugume, Herbert (Kabale University, 2023)
This study examined the effect of digital technologies on financial performance at Kabale District Local Government. The predictor variables under study were integrated financial management systems, programme-based budgeting system and integrated personnel and payroll system, while financial performance was the outcome variable. The study followed a cross-sectional survey design. Data from 139 respondents was collected and analysed quantitatively, complemented with qualitative analysis. Since descriptive analysis entailed description of a single variable and its attributes, frequency tables were used to present the data. At the bivariate level, a Pearson correlation matrix was conducted to ascertain the relationships between the predictor variables and the dependent variable. A linear regression model was used to fit the data. Research findings from the regression model show that integrated financial management systems (R=862), programme-based budgeting system and integrated personnel (R=756 and integrated personnel and payroll system (R=829) have a positive significance on the financial performance at Kabale District local government. The main conclusion drawn from this research is that integrated financial management systems, programme-based budgeting system and integrated personnel and integrated personnel and payroll system have a significant effect on service delivery. The study therefore recommends that there is need to put more efforts on integrated financial management systems, programme-based budgeting system and integrated personnel and integrated personnel and payroll system for fortitudes of making financial performance as a custom at Kabale District Local Government.